Застосування класифікації ШІ-генерованих повідомлень в інтернет-браузерах для боротьби з пропагандою - Іванова, О. С. (ХНУРЕ, 2024)
This work explores the intricate dynamics of propaganda and AI convergence in the contemporary digital era. It highlights the challenges arising from the rapid dissemination of information through digital platforms, blurring the lines between trustworthy news and propaganda. It proposes using a combination of GAN and classification models to detect and combat both human and AI-generated propaganda, advocating for their integration into web browsers for real-time identification of propagandistic content. This approach aims to enhance media literacy and critical thinking skills among users, thereby mitigating the harmful effects of propaganda on public discourse and decision-making processes, ultimately strengthening democratic societies.
Keywords: пропаганда; поширення інформації; класифікація повідомлень